A new interconnect method for radio frequency intra‐chip communications using transistors‐based distributed access. Issue 2 (7th December 2018) - Hamieh, Mohamad; Quintanel, Sébastien; Ariaudo, Myriam; Louët, Yves
Abstract: This paper presents a new radio frequency channel access method to a radio frequency (RF) interconnect for intra‐chip communications. The method overcomes the undesired effects that come from multiple connections in classical methods. It is based on an active access, through transistors associated in a distributed topology. This leads to better properties in terms of reflection and transmission coefficients along the transmission line. This approach is validated by making a deep comparison with the basic existing access methods (eg, direct and capacitive). Measurements on a test circuit using the 0.25 μm SiGe BiCMOS technology confirm the good performance of the proposed access.